Inside Cover: Screening, Synthesis, and In Vitro Evaluation of Vinyl Sulfones as Inhibitors of Complement‐Dependent Cytotoxicity in Neuromyelitis Optica (ChemMedChem 4/2016). (February 2016) - Ju, Eun Ji; Yeon, Seul Ki; Park, Jong‐Hyun; Cheon, So Young; Choi, Ji Won; Ha, Taehwan; Jang, Bo Ko; Kim, Siwon; Kang, Yong Gu; Hwang, Hayoung; Cho, Sung Jin; Cheong, Eunji; et al.
Abstract : The inside cover picture shows a possible docking pose of a potent small‐molecule compound that has blocking activity against the binding of neuromyelitis optica‐specific immunoglobulin G autoantibodies (NMO‐IgG) and aquaporin 4 (AQP4). Neuromyelitis Optica (NMO) is an autoimmune disorder affecting the optic nerve and spinal cord. NMO pathogenesis involves the binding of NMO‐IgG and AQP4 in astrocytes and complement‐dependent cytotoxicity. A screening system was established for inhibitors against the binding of NMO‐IgG to AQP4 in an in vitro model. More information can be found in the Communication by Sung Min Kim, Ki Duk Park et al. onpage 377 in Issue 4, 2016 (DOI: 10.1002/cmdc.201500546).